Oregon's transportation and land use model integration program: A retrospective - Donnelly, Rick (Journal of Transport and Land Use, 2018)
An ambitious and innovative integrated land use-transport modeling system has been developed in Oregon over the past two decades. This work, completed under the Transportation and Land Use Model Integration Program (TLUMIP), included the development of two generations of models and the data required to build and use them and spawned the development of two others that have continued independently. An outreach program and collaborative development of freight data and forecasts were also included, as well as system testing and applications. A brief description of the motivation behind TLUMIP and the resulting modeling systems are presented. Perhaps more interesting is the story behind the models, describing several major model design, institutional, and methodology issues that were overcome. Using an integrated model in practice also entailed addressing a wider range of analytical requirements and stakeholder expectations about usability, accuracy, and extensibility than typically considered in academic pursuits. The key lessons learned through development and use of the models are discussed, with the hope that they will inform the development of similar large-scale modeling systems.